2012
DOI: 10.1002/lary.22490
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind study on clonazepam in patients with burning mouth syndrome

Abstract: Clonazepam appears to have a positive effect on pain in BMS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 21 publications
2
152
0
7
Order By: Relevance
“…A recent placebo-controlled study in 20 BMS patients reported a significant reduction in pain following 0.5 mg of oral clonazepam daily for 9 weeks in this study 28. However, concerns about systemic absorption of topical or systemic therapy, potential dependence especially for systemic clonazepam, and a lack of long-term data limit its potential value in the therapy of BMS.…”
Section: Managementmentioning
confidence: 64%
“…A recent placebo-controlled study in 20 BMS patients reported a significant reduction in pain following 0.5 mg of oral clonazepam daily for 9 weeks in this study 28. However, concerns about systemic absorption of topical or systemic therapy, potential dependence especially for systemic clonazepam, and a lack of long-term data limit its potential value in the therapy of BMS.…”
Section: Managementmentioning
confidence: 64%
“…209 Clonazepam may affect taste sensation. 236,237 Topical clonazepam has been used in the management of neuropathic oral conditions and anecdotal data in taste and smell complaints have been published. 238,239 Topical application, while relatively benign, may be a problem for patients with little or no saliva.…”
Section: Managementmentioning
confidence: 99%
“…7 As clonazepam has strong effects on the brain serotonergic system, it also promotes descending pain inhibition, and suppresses the spontaneous central neuronal hyperactivity due to deafferentation. 50 Although the functions of the GABA-A receptor in the peripheral tissues are poorly understood, one may assume that a change in receptor density or ligand concentration may be related to the burning pain stomatodynia. This change may be triggered by neurosteroid deprivation.…”
Section: Clonazepammentioning
confidence: 99%